Safety and efficacy of the bumped kinase inhibitor BKI-1553 in pregnant sheep experimentally infected with Neospora caninum tachyzoites - Roberto Sánchez-Sánchez; Ignacio Ferre; Michela Re; Patricia Vázquez; Luis Miguel Ferrer; Javier Blanco-Murcia; Javier Regidor-Cerrillo; Manuel Pizarro Díaz; Marta González-Huecas; Enrique Tabanera; Paula García-Lunar; Julio Benavides; et al. (International Journal for Parasitology: Drugs and Drug Resistance, 2018)
Neospora caninum is one of the main causes of abortion in cattle, and recent studies have highlighted its relevance as an abortifacient in small ruminants. Vaccines or drugs for the control of neosporosis are lacking. Bumped kinase inhibitors (BKIs), which are ATP-competitive inhibitors of calcium dependent protein kinase 1 (CDPK1), were shown to be highly efficacious against several apicomplexan parasites in vitro and in laboratory animal models. We here present the pharmacokinetics, safety and efficacy of BKI-1553 in pregnant ewes and foetuses using a pregnant sheep model of N. caninum infection. BKI-1553 showed exposure in pregnant ewes with trough concentrations of approximately 4 μM, and of 1  μM in foetuses. Subcutaneous BKI-1553 administration increased rectal temperatures shortly after treatment, and resulted in dermal nodules triggering a slight monocytosis after repeated doses at short intervals. BKI-1553 treatment decreased fever in infected pregnant ewes already after two applications, resulted in a 37–50% reduction in foetal mortality, and modulated immune responses; IFNγ levels were increased early after infection and IgG levels were reduced subsequently. N. caninum was abundantly found in placental tissues; however, parasite detection in foetal brain tissue decreased from 94% in the infected/untreated group to 69–71% in the treated groups. In summary, BKI-1553 confers partial protection against abortion in a ruminant experimental model of N. caninum infection during pregnancy. In addition, reduced parasite detection, parasite load and lesions in foetal brains were observed. Keywords: Neospora caninum, Sheep, Pregnancy, Treatment, Protein kinase inhibitor, BKI-1553